Economics of land degradation in Niger - Nkonya, Ephraim M.; Ru, Yating; Kato, Edward (Wageningen Academic Publishers, 2018)
Land degradation poses daunting challenges to Niger and the country has designed several policies and strategies for combatting it. Building on work past studies, this study uses new satellite data which have higher resolution and run for longer time – thus capturing the longterm land management dynamics. This study also uses an improved cost of land degradation model which nets out benefits from land improvement as well analysing the impacts of land degradation on food and nutrition security. Results show that in the past 25 years, Niger has rehabilitated over 10 million ha of bare land – or 2.6% of lands south of the desert – home to more than 90% of population. The annual total economic value of degradation was 2015 US$3.535 billion or 19% of the 2015 purchasing power parity gross domestic product. Rehabilitation of degraded land will have large impacts on household food and nutrition security. Yet, adoption rates of key land management practices are very low. The results suggest the need to Niger to find other incentives for increasing adoption of improved land management – such as payment for ecosystem services and improvement of road infrastructure, education and extension services.